Reversion of Hormone Treatment Resistance with the Addition of an mTOR Inhibitor in Endometrial Stromal Sarcoma. (7th July 2014) - Martin-Liberal, J.; Benson, C.; Messiou, C.; Fisher, C.; Judson, I.
Abstract : Background . Endometrial stromal sarcomas (ESS) are a subtype of gynaecological sarcomas characterized by the overexpression of hormone receptors. Hormone treatment is widely used in ESS but primary or acquired resistance is common. The mammalian target of rapamycin (mTOR) pathway has been suggested to play a key role in the mechanisms of hormone resistance. Recent studies in breast and prostate cancer demonstrate that this resistance can be reversed with the addition of an mTOR inhibitor. This phenomenon has never been reported in ESS. Methods . We report the outcome of one patient with pretreated, progressing low grade metastatic ESS treated with medroxyprogesterone acetate in combination with the mTOR inhibitor sirolimus. Results . Partial response was achieved following the addition of sirolimus to the hormone treatment. Response has been maintained for more than 2 years with minimal toxicity and treatment is ongoing. Conclusion . This case suggests that the resistance to the hormone manipulation in ESS can be reversed by the addition of an mTOR pathway inhibitor. This observation is highly encouraging and deserves further investigation.